(untitled) (Teacher’s World: Journal of Education and Research, 2024)
Education is a basic requirement for every human being which is the only means of ensuring human survival, protection, and development. Education is the foundation of society, and educational opportunity, particularly equitable opportunity, is a major concern in the educational system. By 2030, the United Nations has adopted a target (Goal 4) for achieving quality, equitable, and inclusive education for all. Bangladesh has made great progress in terms of the enrolment of children in schools over the last few years. However, a large proportion of children with disabilities have yet to gain access to the educational facilities that they desire. This paper is an attept to focus on the current education status of children with disabilities and identify some key factors that restrict access to their education in Bangladesh. As the paper is based on secondary sources of data, hence, published journal articles, research report, policy documents of government and non-government organization etc. were used to outline. A number of factors influencing the accessibility of education for children with disabilities are discussed here, including parental perception, negative attitudes, school problems, poverty, inaccessibility, flawed curriculum and scarcity of teaching materials, and poor enforcement of policies and laws. Finally, in this paper, some recommendations are made to ensure educational opportunities for children with disabilities by removing barriers to access to education. Teacher’s World: Journal of Education and Research, 49 (1), 175-186